Pembelajaran Berdiferensiasi dan Penguatan Projek Profil Pelajar Pancasila dalam Implementasi Kurikulum Merdeka - Nikmah, Nikmah; Amin, Muhammad; Purnamasari S, Ayu; Simbolon, Parlindungan; Saputra, Waldi; Fadhilatul Hikmah, Wahyu; Tryana, Nofita (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The community service program at SDIT Tahfiz Al-Makki in Siak Hulu, Kampar Regency, focuses on the implementation of the Merdeka Curriculum, with the primary objective of enhancing teachers' abilities in differentiated learning and the integration of Pancasila values in education. Amidst the current educational challenges that necessitate a more innovative and inclusive approach, this program bridges the gap between educational practices and real-world needs. The methods employed include presentations, discussions, and hands-on practices, actively involving teachers as participants. The main outcome of this program is the improved understanding and skills of teachers in applying differentiated learning, as well as the reinforcement of Pancasila values in the learning process. The program has successfully demonstrated increased interaction and a more harmonious relationship between teachers and students, along with the development of student character in line with the Pancasila Student Profile. In conclusion, this service program has achieved its goal of enhancing the quality of education at SDIT Tahfiz Al-Makki, equipping teachers with more effective and relevant learning methods for the current era. This initiative reflects the importance of adaptation and innovation in education to meet the demands of the times and prepare a highly competitive and morally upright future generation.